2020
DOI: 10.3389/fvets.2020.570055
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Dolphin Cardiac Auscultation and Characterization of Heart Murmurs in Managed and Free-Ranging Bottlenose Dolphins (Tursiops truncatus)

Abstract: Cardiac auscultation is an important, albeit underutilized tool in aquatic animal medicine due to the many challenges associated with in-water examinations. The aims of this prospective study were to (1) establish an efficient and repeatable in-water cardiac auscultation technique in bottlenose dolphins ( Tursiops truncatus ), (2) describe the presence and characterization of heart murmurs detected in free-ranging and managed dolphins, and (3) characterize heart murmur etiology through e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Cardiac auscultation was systematically performed as previously described with Navy and free-ranging dolphins [ 1 ]. All auscultations were performed in seawater with the 3M™ Littman® Veterinary Master Classic II 32” (3M™ Littman®, St. Paul, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac auscultation was systematically performed as previously described with Navy and free-ranging dolphins [ 1 ]. All auscultations were performed in seawater with the 3M™ Littman® Veterinary Master Classic II 32” (3M™ Littman®, St. Paul, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Nineteen dolphins were auscultated in SB and 34 in BB by a cardiologist (AH or SMH) in addition to other marine mammal veterinarians (BKL, FMG, CRS) according to standard procedure [ 1 ]. Murmurs were graded by intensity using the conventional Grade I-VI scale [ 45 – 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were no published studies of the cardiovascular system in marine mammals exposed to DWH oil at the time of the workshop, a few studies have been completed in the last year. Linnehan et al (2020) found that marine mammals (managed in San Diego) and wild common bottlenose dolphins (in Sarasota, Florida and Barataria Bay, Louisiana) displayed a similarly high prevalence (approximately 90%) of systolic heart murmurs, with maximal intensity typically in the sternal cranial and left cranial areas of the heart. However, three dolphins in Barataria Bay also exhibited medium mitral regurgitation and moderate to severe lung disease; veterinarians gave all three individuals a guarded to poor prognosis based upon all of the health assessment data available.…”
Section: Marine Mammalsmentioning
confidence: 97%
“…This is consistent with extensive photographic-identification and telemetry research documenting that bay, sound, and estuarine dolphins in the Southeastern U.S. typically stay in relatively small usage areas [e.g., 24 , 26 – 33 ], often despite acute or chronic environmental stressors such as low salinity [ 10 , 19 , 34 ], tropical disturbances [ 21 , 35 ], oil spills and other anthropogenic contaminants [ 10 , 34 , 36 – 38 ], and harmful algal blooms [ 35 , 39 – 42 ]. Due to their high site fidelity, BBES dolphins were exposed to DWH oil in their heavily contaminated habitat and subsequently suffered numerous adverse health effects from oil toxicity (e.g., lung disease, impaired stress response and adrenal dysfunction, immune dysfunction, and poor overall health prognoses), leading to drastic and prolonged elevated reproductive failure rates and mortality rates following the oil spill [ 43 53 ]. NOAA declared a UME related to the effects of DWH oiling on cetaceans throughout the nGOMx, including dolphins in the Barataria Basin [ 51 , 54 ].…”
Section: Introductionmentioning
confidence: 99%